Hammajang luck : a novel - Yamamoto, Makana (Harper Voyager, an imprint of HaperCollinsPublishers, 2025)
"Edie is done with crime. Eight years in prison changes a person -- costs them too much time from too many of the people who need them most. And it's all Angel's fault. She sold Edie out in what should have been the greatest moment of their lives. Instead, Edie was shipped off to the icy prison planet spinning far below the soaring skybridges and neon catacombs of Kepler Space Station -- of home -- to spend the best part of a decade alone. But then a chance for early parole appears out of nowhere and Edie steps into the pallid sunlight to find none other than Angel waiting -- and she has an offer. One last job. One last deal. One last target: the trillionaire tech god they failed to bring down last time. There's just one thihng Edie needs to do -- trust Angel again -- which also happens to be the last thing Edie wants to do. What could possibly go all hammajang about this plan?"--Page 4 of cover.